The Role of Islamic Education in Shaping Tolerance and Interfaith Harmony: A Comprehensive Literature Review - Nurjaman, Fikri; Aminah, Siti (Samarinda International Journal of Islamic Studies, 2024)
This literature review examines the critical role of Islamic education in fostering tolerance and interfaith harmony. The study investigates how Islamic educational practices, curricula, and institutional frameworks can contribute to promoting peaceful coexistence and understanding among diverse religious communities. Drawing upon a wide range of scholarly sources, this review explores the historical and contemporary approaches to Islamic education, analyzing their impact on shaping attitudes toward religious pluralism. The review synthesizes existing research to identify best practices and challenges in the implementation of tolerant and inclusive educational strategies. Key findings highlight the significance of incorporating interfaith dialogue, promoting critical thinking, and addressing prejudice within Islamic educational settings. The review also discusses the influence of religious authorities, the role of educational institutions, and the impact of broader social and political contexts on shaping tolerance. It concludes with recommendations for educators, policymakers, and religious leaders to enhance the effectiveness of Islamic education in fostering interfaith harmony.